Analisis Pendapatan dan Optimalisasi Input Peternak Sapi Potong Rakyat Binaan Sarjana Membangun Desa Wirausahawan Pendamping (Smdwp) yang Berkelanjutan di Kabupaten Tasikmalaya - Sukmayadi, K.; Ismail, A.; Hidayat, A. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
This research aims to estimate income, return-cost ratio (R/C ratio) and input optimization of Sarjana Membangun Desa Wirausahawan Pendamping (SMDWP) assited beef cattle farmers in Tasikmalaya District with different business systems, mainly to observe internalization of externalities by integrating waste management system into their business system. Data collection was conducted in September and October 2016 at SMDWP asissited beef cattle farmers groups in Tasikmalaya District. Quantitative reseach, in which the data were analyzed with statistical analysis by calculating the average income, R/C ratio and Cobb Douglass regression function to observe input optimization. Data collection conducted by census. The results of this research suggest that the highest income estimation and R/C ratio was beef cattle fattening farmers with integrated waste management system which cattle ownership is above 5 AU more, which is Rp.10.275.000 /month and 2,301 respectively. The lowest income estimation and R/C ratio was beef cattle breeding farmers without integrated waste management system which cattle ownership between 3-4 AU, which is Rp.454.127/month and 1,125 respectively. Factors that technically affect the production function was the amount of forages, amount of concentrate feeds, initial cattle weight, cattle breeds. Input application in the beef cattle farming at SMDWP fostered beef cattle farmers groups in Tasikmalaya District are not optimized, which is the amount of forages, amount of concentrate feeds, and initial cattle weight.